POSITIVE EFFECT OF ENTEROSORPTION IN DOXORUBICIN-INDUCED CARDIOHEMODYNAMICS ALTERATION - Shevchuk, O. O.; Portnichenko, G. V.; Lapikova-Bryginska, T. Y.; Goncharov, S. V.; Nikolaev, V. G.; Dosenko, V. E. (International Journal of Medicine and Medical Research, 2020)
Background. Anthracycline antibiotics are one of the most effective anti-cancer drugs, but their cardiotoxicity what limits its therapeutic use. Objective. To analyze the efficiency of enterosorption in doxorubicin-induced cardiohemodynamics violation. Methods. Subchronic doxorubicin toxicity was modeled by injecting the anthracycline antibiotic intraperitoneally at a dose of 5 mg/kg once a week for 4 weeks, in total 20 mg/kg. Male Wistar rats were randomly distributed into 3 groups: control; DOX-group and DOX + enterosorbent C2 rats (γ = 0.18 g/cm3, BET area 2162 m2/g). Cardiohemodynamics was studied by the Millar Instruments, heart morphometry – by Avtandilov’s method. Results. Mortality rate in DOX-group was 25%. Ejection fraction and Stroke work indices were lower compared to the control group, preload adjusted maximal power decreased by 57.6%, minimum volume and end-systolic volume increased by 76,2 and 67.5% respectively. End-systolic stiffness of left ventricle (Emax) as well as arterial elastance (Ea) and end-systolic pressure had tended to decrease. Indices of left ventricle (LV) volume at systole increased: V@dPdtmax – by 73.3%, V@dPdtmin – by 81.9%. End-diastolic volume increased by 54.6%. As for the dPdtmin, and Tau constant we observed the slight tendency to its decline. Endocardial surface of LV increased by 42.7%, Planimetric Index – by 40.4% compared to the control group of rats. In DOX+C2 group mortality rate was 18.75%. We observed the strong tendency to normalization of the main indices compared to the DOX group and shrinking of the LV. We want to underline the positive trends especially in Ejection Fraction (from 39.62±10.50% to 46.23±11.46%) and Stroke Work (from 6406.50±3345.83 to 10363.14±7329.55 mmHg×uL) as important indicators of the effectiveness of cardiac pump function. Conclusions. Enterosorption demonstrated positive impact on the doxorubicin-induced violated cardiohemodynamics and decreased the mortality rate. It is a ground for further investigations.